Cerebral astroblastoma in an adult: An immunohistochemical, ultrastructural and genetic study. Issue 3 (21st September 2012) - Fu, Yong‐Juan; Taniguchi, Yoshinori; Takeuchi, Shigekazu; Shiga, Atsushi; Okamoto, Kouichirou; Hirato, Junko; Nobusawa, Sumihito; Nakazato, Yoichi; Kakita, Akiyoshi; Takahashi, Hitoshi
<x xml:space="preserve">Abstract</x> Astroblastoma is a rare glial tumor of unknown origin, usually affecting the cerebral hemispheres of children and young adults. Here we report an unusual cerebral tumor in a 60‐year‐old woman. On MRI, the tumor appeared as a well circumscribed lesion in the left frontal lobe. Histopathologically, it was composed of rounded eosinophilic cells, and was divisible into two areas. One area was characterized by a collection of GFAP‐positive cells around sclerotic blood vessels (astroblastic pseudorosettes and perivascular hyalinization), and had a Ki‐67 labeling index of 2.8%. However, the other area was highly cellular, showing many GFAP‐negative cells often with a rhabdoid appearance, mitoses and a Ki‐67 index of 15.7%. Thus, a final diagnosis of malignant astroblastoma was made. In both areas of the tumor, nearly all the cells were positive for epithelial membrane antigen, and many were positive for oligodendrocyte transcription factor 2 (Olig2). Focal expression of cytokeratin was also evident. With regard to genetic markers, the tumor cells were positive for INI1 and negative for mutant IDH1. The p53 labeling index was <1%. Ultrastructurally, the presence of intra‐ and intercellular lumina with microvilli was a feature. DNA examination of IDH1/2 and TP53 showed no mutations. In conclusion, although ependymal features were evident ultrastructurally in the present tumor, the immunohistochemical expression pattern of Olig2 was that of diffuse astrocytoma. On the other hand, the absence of mutations in both IDH1/2 and TP53 suggested that the present tumor was not a purely astrocytic neoplasm. Further studies, including molecular and genetic analyses, will provide insight into the histogenesis of astroblastoma.